2013
DOI: 10.1590/s1519-99402013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Parâmetros e tendências genéticas para pesos de várias idades em bovinos Nelore

Abstract: Objetivou-se estimar parâmetros, correlações e tendências genéticas para os pesos de animais da raça Nelore criados na região da Mata e no Agreste Nordestino aos 205 (P205), 365 (P365) e 550 (P550) dias de idade. Para realização das análises genéticas, utilizou-se da metodologia de modelos mistos. O modelo estatístico continha os efeitos aleatórios aditivos diretos, aditivos maternos, ambiente permanente e o erro; efeitos fixos de grupo contemporâneo - fazenda, sexo, estação (água e seca), mês e ano de nascime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
4
4
1
Order By: Relevance
“…In contrast, Santos et al (2012) obtained heritability estimates of 0.51 for year weight and 0.41 for yearling weight, which are higher values than those observed in this study. The maternal additive heritability estimate for weaning weight (0.05) was similar to that obtained by Silva et al (2013), and indicates that the maternal effect had little importance on this weight, and consequently there would be difficulties in improving the maternal ability for this trait by selection, given the genetic antagonism between the direct and maternal effects (correlation of -0.68). Overall, the direct heritability estimates for body weight at the different evaluated ages were of moderate magnitude, indicating that the additive genetic variabilities would be sufficient to provide responses to selection.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…In contrast, Santos et al (2012) obtained heritability estimates of 0.51 for year weight and 0.41 for yearling weight, which are higher values than those observed in this study. The maternal additive heritability estimate for weaning weight (0.05) was similar to that obtained by Silva et al (2013), and indicates that the maternal effect had little importance on this weight, and consequently there would be difficulties in improving the maternal ability for this trait by selection, given the genetic antagonism between the direct and maternal effects (correlation of -0.68). Overall, the direct heritability estimates for body weight at the different evaluated ages were of moderate magnitude, indicating that the additive genetic variabilities would be sufficient to provide responses to selection.…”
Section: Resultssupporting
confidence: 63%
“…Genetic correlation values observed in this study were close to those obtained by Yokko et al (2007). Silva et al (2013) found positive estimates of genetic correlation of average magnitude (0.55) between weaning and yearling weights; a high correlation (0.80) between weaning weight and year weight; and a correlation of 0.85 between year and yearling weights. Additionally, genetic correlations between W210; W365 and W550 were all higher than 0.85, indicating that heavier animals at weaning responded with greater weights at later ages.…”
Section: Resultsmentioning
confidence: 92%
“…Boligon et al (2010), who assumed 3.0 SDs for outlier removal and a minimum of 4 animals per CG; and by Laureano et al (2011) and Lopes et al (2013), who used a CG with at least 3 animals. Silva et al (2013) adopted at least 9 animals per CG and found maternal heritability estimates lower (0.03) than those observed in all the data sets evaluated in the present study.…”
Section: Resultscontrasting
confidence: 77%
“…This shows that, by using at least 15 animals per CG in genetic evaluations, a higher genetic gain is expected (Figure 2). Yooko et al (2010) found h 2 equal to 0.22 when using a CG with at least 8 animals and 3.0 SDs, whereas Silva et al (2013) reported h 2 equal to 0.13 adopting a CG with at least 9 animals. These and the estimates obtained in the present work are lower than those of 0.23-0.61 observed in other studies, which considered different criteria for outlier removal: minimum of 5 animals per CG (Boligon et al, 2008); minimum of 4 animals per CG and 3.0 SDs (Boligon et al, 2009); minimum of 4 animals per CG (Laureano et al, 2011); and minimum of 3 animals per CG (Lopes et al, 2013 Matos et al (2013), using 3.0 SDs for outlier removal and a CG with at least 7 animals.…”
Section: Resultsmentioning
confidence: 97%
“…These authors, conducting studies using the Bayesian analysis and Nelore animals found results of 0.49. Previous studies by Gonçalves et al (2011) and Silva et al (2013) have also estimated, for Nelore cattle, higher heritability than those found in this study for P365. The mean values estimated for direct heritability of P450 had high magnitude, 0.33, the same has been found by Faria et al (2007) and Sena et al (2013).…”
Section: Resultssupporting
confidence: 60%